OPPRESSION AGAINST CHILDREN IN IWAN FALS SONG LYRICS - Ineu Munawaroh, - (2011)
This research paper entitled 'Oppression Against Children in Iwan Fals Song Lyrics' aims to identify how oppression against children is represented and what types of oppression as evidenced in the texts. The data are in the forms of words, phrases, and sentences in the song lyrics that were purposively selected to answer the research questions. A semiotic theory proposed by Barthes's is used as a tool to analyze the denotative and connotative meanings of symbols as evidenced in the texts and theory of oppression types by Young (1990).The study is descriptive qualitative and uses textual analysis.The findings reveal that oppression against children is represented by children being exploited, ignored, marginalized, and neglected. The analysis also revealed three types of oppression; exploitation, marginalization, and powerlesness as evidenced in the texts. The study concludes that song lyrics are the reflection of today's social life. Children usually become the major victims because children are considered to be weak. The phenomenon of oppression toward children clearly shows that injustice happens when adults misuse their power.